The retake - Calonita, Jen (Delacorte Press, 2020)
"Zoe knows that the only thing harder than middle school is losing a best friend. She and Laura used to do everything together from taking silly selfies, to joining all the same clubs together and even throwing surprise birthday parties for one another. But lately things have been weird between them. Now Laura will post a photo of her hanging out with other girls before responding to Zoe's simple text. She doesn't even want to sit with her at lunch anymore. Zoe is heartbroken--all she wants is for things to go back to normal. But then a magical app downloads on her phone...and things get even weirder! Suddenly Zoe can travel back in time to moments where her and Laura started drifting apart. It is like a dream come true. A chance for Zoe to mend their friendship. But as Zoe goes back to moments of middle school drama--sleepover games gone wrong, field trips with cliques and crushes, and school projects that bring on more-than-awkward encounters--she realizes that second chances don't always go as planned and that sometimes you need to trust the magic of new beginnings"--